Lithospheric Thickness Recovery from Horizontal and Vertical Land Uplift Rates - Vermeer, Martin; Kollo, Karin (Journal of Geodynamics, 2010)
International audience As a result of the BIFROST studies of the Fennoscandian postglacial rebound, it is known that in addition to uplift, there also exists a horizontal movement of the Earth's surface, so that points on it move away from the uplift centre at a rate of about 10% of that of the uplift. We aim to study the vertical and horizontal postglacial motion in order to determine the lithospheric thickness from observed rates. We conjecture that the cause of the radial movement is that, while a thin lithosphere will move up radially from the Earth's centre, in the case of a thick lithosphere, the mantle blocks may slightly rotate due to the land uplift gradient. This phenomenon is investigated and modelled for further analysis. In the computations, the BIFROST dataset for Fennoscandia is used to test our hypothesis. Unfortunately for the North-American land uplift area our method did not produce reasonable results; we suspect one reason is the fragmented nature of the lithosphere in this area.